Design method and preparation method of single-crystal calcium fluoride substrate 3.7-4.8 [mu] m antireflection film
By designing the alternate film layer structure of Y2O3, ZnS, and YF3 on a single-crystal calcium fluoride substrate, the film thickness is optimized, and the problem of insufficient light transmittance in the 3.7-4.8μm band is solved, and the adhesion and Stability enables the application of high-precision optical systems.
Patent Information
- Application Number
- CN202411279966.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-12
AI Technical Summary
The lack of light transmittance of single-crystal calcium fluoride in the 3.7-4.8 μm band limits its application in high-precision optical systems, and its adhesion and stability are insufficient.
Three films are adopted: Y2O3, ZnS, and YF3. ZnS and YF3 are combined with a single crystal calcium fluoride substrate as high and low refractive index materials to design an alternating film layer structure, and the film layer thickness is optimized through the control computer of the coating machine to improve the permeability. overrespect and adhesion.
The transmittance of the 3.7-4.8μm induced film of a single-crystal calcium fluoride substrate meets the requirements, and improves the adhesion and stability of the overall film system. The average transmittance is greater than 99.5%, meeting the needs of high-precision optical systems. .
Smart Images

Figure CN119247525A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of infrared coating technology, and more specifically to a design method and a preparation method of a 3.7-4.8 μm anti-reflection film on a single crystal calcium fluoride substrate. Background Art
[0002] As an excellent light-transmitting material, single-crystal calcium fluoride is widely used in the field of infrared optics. However, due to its high refractive index, its transmittance in a specific band is insufficient, which limits its application in some high-precision optical systems. Therefore, how to improve the transmittance of single-crystal calcium fluoride in the 3.7-4.8μm band has become an urgent problem to be solved in the field of optical thin films. Summary of the invention
[0003] In view of the problems existing in the background technology, an object of the present disclosure is to provide a design method and a preparation method for a 3.7-4.8 μm anti-reflection film on a single crystal calcium fluoride substrate, which can ensure that the transmittance of the designed and prepared 3.7-4.8 μm anti-reflection film on a single crystal calcium fluoride substrate meets the requirements.
[0004] Another object of the present disclosure is to provide a design method and a preparation method for a 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate, which can improve the adhesion and stability of the overall film system.
[0005] Thus, a design method for a 3.7-4.8 μm anti-reflection film on a single crystal calcium fluoride substrate comprises the following steps: Sa, selecting 4 μm as a reference wavelength for designing a 1 / 4 wavelength film thickness of the optical film, and using the film stack formula: Sub / 0.03Q / 0.3H / 0.4L / H / L / 0.15H / AIR, wherein Sub is a single crystal calcium fluoride substrate, AIR represents air, H represents a high refractive index material ZnS (zinc sulfide) with a thickness of 1 / 4 wavelength, and L represents a low refractive index material YF3 (yttrium fluoride) with a thickness of 1 / 4 wavelength; Q represents a film layer base material Y2O3 (yttrium oxide) with a thickness of 1 / 4 wavelength; Sb, calculating and optimizing the film layer thickness through design software to obtain the best film layer thickness, and the optimized transmittance of the single crystal calcium fluoride substrate in the 3.7-4.8 μm band meets the requirements; Sc, inputting the optimized film layer thickness into the control computer of the coating machine.
[0006] A method for preparing a 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate comprises the following steps: S1, cleaning the accompanying plated sheet and the product of the single crystal calcium fluoride substrate as a lens before plating, and preparing three kinds of film materials: ZnS, YF3, and Y2O3; S2, configuring the film system process parameters, wherein the film system process parameter configuration includes the optimal film thickness of the film layer, the evaporation mode of the film material, the deposition rate of the film material, and the use of ion source assisted deposition. The film thickness in the film system process parameters is based on the aforementioned storage in the control of the coating machine. The computer calculates the optimal film thickness of the film layer; S3, puts the cleaned lens into the fixture, hangs the fixture with the lens into the cavity of the coating machine, and performs vacuum baking, pre-melting of the film material, degassing, impurity removal and constant temperature; S4, ion source cleaning of the lens; S5, film coating and monitoring, and coating the film layer on the first side of the lens according to the film system parameter process configuration of step S2; S6, maintaining a constant temperature after coating; S7, cooling and taking out the piece; S8, repeating steps S1 to S7, and coating the film layer on the second side of the lens.
[0007] The beneficial effects of the present disclosure are as follows.
[0008] In the design method and preparation method of the single crystal calcium fluoride substrate 3.7-4.8μm anti-reflection film according to the present disclosure, by using three kinds of film materials, Y2O3, ZnS, and YF3, ZnS and YF3 as high and low refractive index materials, Y2O3 is selected as the base material in combination with the single crystal calcium fluoride substrate, and ZnS and YF3 form the alternating second to sixth layers, the transmittance of the designed single crystal calcium fluoride substrate 3.7-4.8μm anti-reflection film can meet the requirements.
[0009] In the design method and preparation method of the 3.7-4.8μm anti-reflection film on a single crystal calcium fluoride substrate according to the present disclosure, Y2O3 is selected as a base material in combination with the single crystal calcium fluoride substrate. When the film system composed of three film materials, Y2O3, ZnS, and YF3, and the single crystal calcium fluoride substrate meet the transmittance requirement of 3.7-4.8μm, the adhesion and stability of the overall film system can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 It is a schematic structural diagram of a film stack design optimization diagram according to the design method of a 3.7-4.8 μm anti-reflection film on a single crystal calcium fluoride substrate disclosed in the present invention.
[0011] Figure 2 It is a transmittance curve diagram of the film stack design optimization diagram of the design method of the single crystal calcium fluoride substrate 3.7-4.8μm anti-reflection film of Example 1.
[0012] Figure 3It is a curve diagram of the transmittance in the 3.7-4.8 μm band of the accompanying coating sheet of Example 1 coated with 3.7-4.8 μm antireflection films on both sides. DETAILED DESCRIPTION
[0013] It will be understood that the disclosed embodiments are merely examples of the present disclosure, which may be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present disclosure in various ways.
[0014] [Design method of 3.7-4.8μm antireflection film on single crystal calcium fluoride substrate]
[0015] The design method of the 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate disclosed in the present invention comprises the following steps:
[0016] Sa, 4μm is selected as the reference wavelength for the design of 1 / 4 wavelength film thickness of optical thin films, using the film stack formula:
[0017] Sub / 0.03Q / 0.3H / 0.4L / H / L / 0.15H / AIR,
[0018] Wherein, Sub is a single crystal calcium fluoride substrate, AIR represents air, H represents a high refractive index material ZnS (zinc sulfide) with a thickness of 1 / 4 wavelength, L represents a low refractive index material YF3 (yttrium fluoride) with a thickness of 1 / 4 wavelength; Q represents a film layer base material Y2O3 (yttrium oxide) with a thickness of 1 / 4 wavelength;
[0019] Sb, the film thickness is calculated and optimized by design software to obtain the best film thickness. The transmittance of the optimized single crystal calcium fluoride substrate in the 3.7-4.8μm band meets the requirements;
[0020] Sc, the optimized film thickness is input into the control computer of the coating machine.
[0021] In the design method of a 3.7-4.8 μm anti-reflection film on a single crystal calcium fluoride substrate according to the present disclosure, by using three kinds of film materials, Y2O3, ZnS, and YF3, ZnS and YF3 as high and low refractive index materials, Y2O3 is selected as a base material in combination with a single crystal calcium fluoride substrate, and ZnS and YF3 form alternating second to sixth layers, the transmittance of the designed single crystal calcium fluoride substrate 3.7-4.8 μm anti-reflection film can meet the requirements.
[0022] In the design method of a 3.7-4.8 μm anti-reflection film on a single-crystal calcium fluoride substrate according to the present disclosure, Y2O3 is selected as a base material in combination with a single-crystal calcium fluoride substrate. When a film system composed of three film materials, Y2O3, ZnS, and YF3, and a single-crystal calcium fluoride substrate meet the transmittance requirement of 3.7-4.8 μm, the adhesion and stability of the overall film system can be improved.
[0023] In one example, in step Sb, for each of the two sides of the single crystal calcium fluoride substrate, the optimal film thickness is: the film thickness of the first Y2O3 film layer is 15±3nm, the film thickness of the second ZnS film layer is 144.89±3nm, the film thickness of the third YF3 film layer is 268.44±3nm, the film thickness of the fourth ZnS film layer is 500.47±3nm, the film thickness of the fifth YF3 film layer is 671.43±3nm, and the film thickness of the sixth ZnS film layer is 65±5nm, as shown in FIG. Figure 1 For each of the two sides of the single crystal calcium fluoride substrate, the overall thickness of the film structure formed by the six film layers is 1665.23±20nm.
[0024] Accordingly, in one example, in step Sb, the transmittance of the optimized single crystal calcium fluoride substrate in the 3.7-4.8 μm band is greater than 99.5% on average.
[0025] In step Sb, the design software may be, but is not limited to, TFCalc, Essential Macleod, OptiLayer, Filmstar, Filmmaster, and Autofilm.
[0026] [Method for preparing 3.7-4.8μm antireflection film on single crystal calcium fluoride substrate]
[0027] The method for preparing a 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate according to the present disclosure comprises the following steps:
[0028] S1, before plating, clean the accompanying plating sheet and products of the single crystal calcium fluoride substrate used as the lens, and prepare the three types of film materials: ZnS, YF3, and Y2O3;
[0029] S2, film system process parameter configuration, the film system process parameter configuration includes the optimal film thickness of the film layer, the evaporation mode of the film material, the deposition rate of the film material, and the use of ion source assisted deposition. The film thickness in the film system process parameters is based on the aforementioned optimal film thickness stored in the control computer of the coating machine;
[0030] S3, put the cleaned lens into the fixture, hang the fixture with the lens into the cavity of the coating machine, vacuum bake, pre-melt the film material, release air, remove impurities and keep the temperature constant;
[0031] S4, ion source cleaning lens;
[0032] S5, coating and monitoring the film layer, coating the film layer on the first surface of the lens according to the film system parameter process configuration of step S2;
[0033] S6, constant temperature maintenance after plating;
[0034] S7, cooling and picking up;
[0035] S8, repeating steps S1 to S7 to perform film coating on the second surface of the lens.
[0036] In the method for preparing a 3.7-4.8 μm anti-reflection film on a single crystal calcium fluoride substrate according to the present disclosure, the thickness of the film layer in the film system process parameters of step S1 to step S8 and step S2 is based on the optimal film thickness of the film layer stored in the control computer of the coating machine according to the design method of the 3.7-4.8 μm anti-reflection film on a single crystal calcium fluoride substrate according to the present disclosure, so that the transmittance of the prepared 3.7-4.8 μm anti-reflection film on the single crystal calcium fluoride substrate meets the requirements.
[0037] Similarly, in the method for preparing a 3.7-4.8 μm anti-reflection film on a single-crystalline calcium fluoride substrate according to the present disclosure, by selecting Y2O3 as a base material in combination with a single-crystalline calcium fluoride substrate, when a film system composed of three film materials, Y2O3, ZnS, and YF3, and a single-crystalline calcium fluoride substrate meet the transmittance requirement of 3.7-4.8 μm, the adhesion and stability of the overall film system can be improved.
[0038] The cleaning in step S1 is beneficial to improving the surface conditions of the first and second surfaces of the lens, and is helpful to improving the bonding performance between the film structure on each surface and the corresponding surface of the lens. For example, ultrasonic or hand wiping is used to clean the surface of the lens. For example, the thickness of the accompanying plating sheet is 1.0 mm.
[0039] In one example, in step S2, the thickness of the film layer in the film system process parameters is based on the thickness of the optimal film layer stored in the control computer of the coating machine, that is, for each of the two sides of the single crystal calcium fluoride substrate, the thickness of the optimal film layer is: the thickness of the first Y2O3 film layer is 15±3nm, the thickness of the second ZnS film layer is 144.89±3nm, the thickness of the third YF3 film layer is 268.44±3nm, the thickness of the fourth ZnS film layer is 500.47±3nm, the thickness of the fifth YF3 film layer is 671.43±3nm, and the thickness of the sixth ZnS film layer is 65±5nm; the evaporation mode of the film material is that Y2O3 is evaporated by electron beam heating, and ZnS and YF3 are evaporated by resistance heating; the deposition rate of the film material is: the deposition rate of the Y2O3 film layer is The deposition rate of the ZnS film is The deposition rate of the YF3 film is The use of ion source assisted deposition is: all layers of film are plated using ion source assisted deposition. Using ion source assisted deposition can make the corresponding film layer denser and more uniform.
[0040] Furthermore, in one example, the ion source parameters when coating the Y2O3 film layer are: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 180V, anode current 1.8A, argon flow rate in the neutralization gas is 20%, and oxygen flow rate in the neutralization gas is 80%; the ion source parameters when coating the entire ZnS film layer are: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 120V, anode current 1.2A, and argon flow rate in the neutralization gas is 100%; the ion source parameters when coating the entire YF3 film layer are: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 100V, anode current 1A, and argon flow rate in the neutralization gas is 100%.
[0041] The baking in step S3 is to prepare the temperature for the pre-melting of the film material. The pre-melting of the film material can release the gas in the film material and remove the impurities in the film material to ensure the purity of the film material, thereby reducing the adverse factors that affect the quality of the film layer during the film coating process in step S5 described later. In addition, baking also heats the lens. Specifically, in step S3, the temperature of the chamber of the coating machine is set to 180°C; when the vacuum reaches (4.0-6.0)×10 -3 The film material is pre-melted at Pa. After the pre-melting of the film material is completed, the temperature of the cavity of the coating machine reaches 180°C and is kept constant for 10 minutes.
[0042] The ion source cleaning in step S4 uses ion bombardment to clean the surface microstructure of the lens, which can eliminate the oxide layer on the surface of the lens, making the surface of the lens cleaner and conducive to the firm adhesion and growth of the film layer. Specifically, in one example, in step S4, when the vacuum degree reaches (0.9-1.0)×10 -3 Pa, start the ion source of the vacuum coating machine, set the ion cleaning parameters of the ion source as follows: neutralization current 0.8-1.0A, neutralization gas flow 8-10sccm, anode voltage 200-220V, anode current 2-2.5A, argon flow in neutralization gas 100%, and cleaning time 5-8min.
[0043] In one example, in step S5, argon gas is introduced and vacuum is drawn to maintain a constant vacuum when each film layer is deposited, and the constant vacuum is set to be no less than 5.0×10 -3Pa; The first layer of Y2O3 film is deposited when the chamber temperature of the coating machine is raised to 180°C. After the first layer of Y2O3 film is deposited, the chamber temperature of the coating machine is cooled to 150°C and kept constant for 5 minutes. Then, the second to sixth layers of film are deposited at a chamber temperature of 150°C. The deposition of the first layer of film at 180°C is beneficial to the adhesion and stability of the entire film system. In one example, the crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the replaced crystal oscillator among the multiple crystal oscillators, and the crystal oscillator frequency is not less than 5.7MHz.
[0044] In one example, in step S6, after plating is completed, the chamber is kept at a constant temperature of 150°C for 5 minutes to release the internal stress of the film structure.
[0045] In one example, in step S7, the door is opened to take out the items after the temperature drops below 90°C.
[0046] [test]
[0047] Example 1
[0048] Part 1: Design method of 3.7-4.8μm antireflection film on single crystal calcium fluoride substrate
[0049] The design method of the 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate of Example 1 adopts the following steps:
[0050] Sa, 4μm is selected as the reference wavelength for the design of 1 / 4 wavelength film thickness of optical thin films, using the film stack formula:
[0051] Sub / 0.03Q / 0.3H / 0.4L / H / L / 0.15H / AIR,
[0052] Wherein, Sub is a single crystal calcium fluoride substrate, AIR represents air, H represents a high refractive index material ZnS (zinc sulfide) with a thickness of 1 / 4 wavelength, L represents a low refractive index material YF3 (yttrium fluoride) with a thickness of 1 / 4 wavelength; Q represents a film layer base material Y2O3 (yttrium oxide) with a thickness of 1 / 4 wavelength;
[0053] Sb, the film thickness is calculated and optimized by design software to obtain the best film thickness. The transmittance of the optimized single crystal calcium fluoride substrate in the 3.7-4.8μm band meets the requirements;
[0054] Sc, input the optimized film thickness into the control computer of the coating machine;
[0055] Wherein, in step Sb, for each of the two sides of the single crystal calcium fluoride substrate, the optimal film thickness of the film layer is:
[0056] The thickness of the first Y2O3 film is 15nm.
[0057] The thickness of the second ZnS film is 144.89nm.
[0058] The thickness of the third YF3 film is 268.44nm.
[0059] The thickness of the fourth ZnS film layer is 500.47nm.
[0060] The thickness of the fifth YF3 film is 671.43nm.
[0061] The thickness of the sixth ZnS film layer is 65 nm;
[0062] Wherein, in step Sb, the design software is TFCalc.
[0063] Part II: Preparation method of 3.7-4.8μm antireflection film on single crystal calcium fluoride substrate
[0064] The method for preparing the 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate of Example 1 adopts the following steps:
[0065] S1, before plating, ultrasonic cleaning is used for the accompanying plating sheet and products of the single crystal calcium fluoride substrate used as the lens, and three kinds of film materials, namely ZnS, YF3 and Y2O3, are prepared. The thickness of the accompanying plating sheet is 1.0mm;
[0066] S2, the vacuum coating machine is a vacuum coating machine with a Hall ion source equipped with a neutralizer manufactured and sold by Chengdu Siwork Vacuum Technology Co., Ltd. The Hall ion source equipped with a neutralizer was purchased from Boton Optoelectronics Technology Co., Ltd. The film system process parameter configuration includes the optimal film thickness of the film layer, the evaporation mode of the film material, the deposition rate of the film material, and the use of ion source assisted deposition. The thickness of the film layer in the film system process parameters is based on the optimal film thickness stored in the control computer of the coating machine in the first part above. The evaporation mode of the film material is that Y2O3 uses electron beam heating evaporation, and ZnS and YF3 use resistance heating evaporation; the deposition rate of the film material is: the deposition rate of the Y2O3 film layer is The deposition rate of the ZnS film is The deposition rate of the YF3 film is The use of ion source assisted deposition is as follows: all layers of the film are plated using ion source assisted deposition; the ion source parameters when plating the Y2O3 film are as follows: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 180V, anode current 1.8A, argon flow rate in the neutralization gas is 20%, and oxygen flow rate in the neutralization gas is 80%; the ion source parameters when plating all ZnS film layers are as follows: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 120V, anode current 1.2A, and argon flow rate in the neutralization gas is 100%; the ion source parameters when plating all YF3 film layers are as follows: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 100V, anode current 1A, and argon flow rate in the neutralization gas is 100%.
[0067] S3, put the cleaned lens into the fixture, hang the fixture with the lens into the cavity of the coating machine, vacuum bake, pre-melt the film material, degas, remove impurities and keep the temperature constant. The temperature of the cavity of the coating machine is set to 180℃. When the vacuum reaches 4.0×10 -3 The film material is pre-melted at Pa. After the pre-melting of the film material is completed, the temperature of the cavity of the coating machine reaches 180°C and is kept constant for 10 minutes.
[0068] S4, ion source cleaning lens, when the vacuum reaches 1.0×10 -3 Pa, start the ion source of the vacuum coating machine, and set the ion cleaning parameters of the ion source as follows: neutralization current 1.0A, neutralization gas flow rate 10sccm, anode voltage 220V, anode current 2A, argon gas flow rate in neutralization gas 100%, and cleaning time 8min;
[0069] S5, film coating and monitoring, according to the film system parameter process configuration of step S2, the film layer is coated on the first surface of the lens, and argon gas is introduced and vacuumed to maintain the flow type constant vacuum when coating each film layer. The constant vacuum degree is set to 5.0×10 -3 Pa, the first layer of Y2O3 film is deposited at a temperature of 180°C in the cavity of the coating machine. After the first layer of Y2O3 film is deposited, the cavity of the coating machine is cooled to 150°C and kept at a constant temperature for 5 minutes. Then, the second to sixth layers are deposited at a cavity of 150°C in the coating machine. The crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the replaced crystal oscillator among the multiple crystal oscillators, and the crystal oscillator frequency is 6MHz.
[0070] S6, after plating is completed, the cavity is kept at a constant temperature of 180°C for 5 minutes;
[0071] S7, wait until the temperature drops to 90°C, open the door and take out the items;
[0072] S8, repeating steps S1 to S7 to perform film coating on the second surface of the lens.
[0073] Comparative Example 1
[0074] Except that the innermost Y2O3 layer (ie, the first film layer) and the plating of the innermost Y2O3 layer are omitted in the first part and the second part, the rest is the same as in Example 1.
[0075] Comparative Example 2
[0076] Except that in step S5 of the second part, the first Y2O3 film layer is evaporated at a chamber temperature of 150°C of the coating machine, the rest is the same as in Example 1.
[0077] Figure 3 The curve diagram of the transmittance in the 3.7-4.8 μm band of the accompanying plate of Example 1 coated with 3.7-4.8 μm antireflection film on both sides. Figure 3 It can be seen that the transmittance of the prepared single crystal calcium fluoride substrate in the 3.7-4.8 μm band is greater than 99.5% on average.
[0078] According to GJB2485A-2019, the following tests were performed after coating on both sides of Example 1, Comparative Example 1 and Comparative Example 2.
[0079] Water bubble test: Take tap water to conduct a water bubble test for 2 hours to observe whether the film layer on each surface falls off from the accompanying plating sheet and whether the film layer on each surface is cracked.
[0080] Salt spray test: neutral salt spray test for 48 hours, observe whether the film layer on each side of the accompanying plating sheet falls off, observe whether the film layer on each side of the accompanying plating sheet cracks.
[0081] Adhesion test: Use hand to stick 3M tape on each side of the plating sheet and pull the tape in the direction opposite to the sticking end to observe whether the film layer is pulled up.
[0082] Thermal shock test: In a high and low temperature box, perform thermal shock test in the range of -40℃ to 85℃ for 24 hours to observe whether the film layers on each side of the accompanying plating sheet fall off or crack.
[0083] Constant temperature and humidity test: In a constant temperature and humidity chamber, at 50°C and 95% relative humidity for 48 hours, observe whether the film layers on each side of the accompanying plating sheet fall off or crack.
[0084] Low temperature test: In a low temperature box, at -40℃ for 48h, observe whether the film layers on each side of the accompanying plating sheet fall off, and observe whether the film layers on each side of the accompanying plating sheet crack.
[0085] High temperature test: In a high temperature box, at 85℃ for 48h, observe whether the film layers on each side of the accompanying plating sheet fall off, and observe whether the film layers on each side of the accompanying plating sheet crack.
[0086] Table 1 shows the transmittance of Example 1 and Comparative Examples 1-2 and the results of various tests.
[0087] Table 1 Transmittance of Example 1 and Comparative Examples 1-2 and results of various tests
[0088]
[0089]
[0090] It can be seen from Comparative Example 1 and Example 1 that Comparative Example 1 did not use Y2O3 as the base coating film layer of the substrate, the adhesion test failed, and the firmness did not meet the GJB2485A-2019 acceptance standard.
[0091] It can be seen from Comparative Example 2 and Example 1 that the temperature during the plating of the Y2O3 film layer of Comparative Example 2 is lower than that of Example 1, and both the salt spray test and the constant temperature and humidity test were failed, indicating that the durability of the film layer cannot be maintained in a long-term hot and humid environment and salt spray environment. The heating of Example 1 (under ion source assisted deposition) can effectively optimize the growth conditions of the thin film, making the Y2O3 film layer more firmly bonded to the substrate, thereby ensuring the overall stability of the film layer.
[0092] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.
Claims
1. A design method for a 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate, characterized in that: Includes steps: Sa, 4μm is selected as the reference wavelength for the design of 1 / 4 wavelength film thickness of optical thin films, using the film stack formula: Sub / 0.03Q / 0.3H / 0.4L / H / L / 0.15H / AIR, Wherein, Sub is a single crystal calcium fluoride substrate, AIR represents air, H represents a high refractive index material ZnS (zinc sulfide) with a thickness of 1 / 4 wavelength, L represents a low refractive index material YF3 (yttrium fluoride) with a thickness of 1 / 4 wavelength; Q represents a film layer base material Y2O3 (yttrium oxide) with a thickness of 1 / 4 wavelength; Sb, the film thickness is calculated and optimized by design software to obtain the best film thickness. The transmittance of the optimized single crystal calcium fluoride substrate in the 3.7-4.8μm band meets the requirements; Sc, the optimized film thickness is input into the control computer of the coating machine.
2. The design method of a 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate according to claim 1, characterized in that: In step Sb, for each of the two sides of the single crystal calcium fluoride substrate, the optimal film thickness of the film layer is: The thickness of the first Y2O3 film is 15±3nm. The thickness of the second ZnS film is 144.89±3nm. The thickness of the third YF3 film is 268.44±3nm. The thickness of the fourth ZnS film layer is 500.47±3nm. The thickness of the fifth YF3 film is 671.43±3nm. The thickness of the sixth ZnS film layer is 65±5nm; In step Sb, the transmittance of the optimized single crystal calcium fluoride substrate in the 3.7-4.8 μm band is greater than 99.5% on average.
3. The design method of a 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate according to claim 1, characterized in that: In step Sb, the design software is TFCalc, Essential Macleod, OptiLayer, Filmstar, Filmmaster, and Autofilm.
4. A method for preparing a 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate, characterized in that: Includes steps: S1, before plating, clean the accompanying plating sheet and products of the single crystal calcium fluoride substrate used as the lens, and prepare the three types of film materials: ZnS, YF3, and Y2O3; S2, film system process parameter configuration, the film system process parameter configuration includes the optimal film thickness of the film layer, the evaporation mode of the film material, the deposition rate of the film material, and the use of ion source assisted deposition, and the film thickness of the film system process parameters is based on the optimal film thickness of the film layer stored in the control computer of the coating machine according to any one of claims 1-3; S3, put the cleaned lens into the fixture, hang the fixture with the lens into the cavity of the coating machine, vacuum bake, pre-melt the film material, release air, remove impurities and keep the temperature constant; S4, ion source cleaning lens; S5, coating and monitoring the film layer, coating the film layer on the first surface of the lens according to the film system parameter process configuration of step S2; S6, constant temperature maintenance after plating; S7, cooling and picking up; S8, repeating steps S1 to S7 to perform film coating on the second surface of the lens.
5. The method for preparing a 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate according to claim 1, characterized in that: In step S1, Cleaning is done by ultrasonic cleaning and manual wiping; The thickness of the accompanying plating sheet is 1.0 mm.
6. The method for preparing a 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate according to claim 1, characterized in that: In step S2, The thickness of the film layer in the film system process parameters is based on the optimal film thickness of the film layer stored in the control computer of the coating machine according to claim 2; The evaporation mode of the film material is that Y2O3 uses electron beam heating evaporation, and ZnS and YF3 use resistance heating evaporation; The deposition rate of the film material is: The deposition rate of the Y2O3 film layer is The deposition rate of the ZnS film is The deposition rate of the YF3 film is The use of ion source assisted deposition is: all layers of film are plated using ion source assisted deposition.
7. The method for preparing a 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate according to claim 6, characterized in that: The ion source parameters when depositing the Y2O3 film are: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 180V, anode current 1.8A, argon flow rate in neutralization gas 20%, and oxygen flow rate in neutralization gas 80%. The ion source parameters when coating all ZnS film layers are: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 120V, anode current 1.2A, and argon gas flow rate in neutralization gas is 100%; The ion source parameters when coating all YF3 film layers are: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 100V, anode current 1A, and argon flow rate in neutralization gas is 100%.
8. The method for preparing a 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate according to claim 4, characterized in that: In step S3, The temperature of the coating machine chamber is set to 180°C; When the vacuum reaches (4.0-6.0)×10 -3 The film material is pre-melted at Pa. After the pre-melting of the film material is completed, the temperature of the cavity of the coating machine reaches 180°C and is kept constant for 10 minutes.
9. The method for preparing a 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate according to claim 4, characterized in that: In step S4, When the vacuum degree reaches (0.9-1.0)×10 -3 Pa, start the ion source of the vacuum coating machine, The ion cleaning parameters of the ion source were set as follows: neutralization current 0.8-1.0 A, neutralization gas flow rate 8-10 sccm, anode voltage 200-220 V, anode current 2-2.5 A, argon flow rate in neutralization gas 100%, and cleaning time 5-8 min.
10. The method for preparing a 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate according to claim 4, characterized in that: In step S5, When coating each film layer, argon gas is introduced and vacuum is drawn to maintain the flow type constant vacuum, and the constant vacuum is set to no less than 5.0×10 -3 Pa; The first Y2O3 film layer is deposited when the chamber temperature of the coating machine is raised to 180°C. After the first Y2O3 film layer is deposited, the chamber temperature of the coating machine is lowered to 150°C for 5 minutes, and then the second to sixth film layers are deposited when the chamber temperature of the coating machine is 150°C. The crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator pieces of the multiple crystal oscillator pieces of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the replaced crystal oscillator pieces among the multiple crystal oscillator pieces, and the crystal oscillator frequency is not less than 5.7MHz.
11. The method for preparing a 3.7-4.8 μm antireflection film on a single crystal calcium fluoride substrate according to claim 4, characterized in that: In step S6, after the plating is completed, the cavity is kept at a constant temperature of 150°C for 5 minutes; In step S7, the door is opened to take out the items when the temperature drops below 90°C.
Citation Information
Patent Citations
Medium-wave infrared anti-reflection film design and preparation method
CN110794490A
Preparation method for plating antireflection film system on chalcogenide glass substrate
CN116282962A
CaF2 substrate-based infrared narrow-band-pass wide-cut-off-band high-optical-density optical filter
CN116819666A
Manufacturing method of infrared glued beam splitter prism
CN117388966A
Preparation method for plating two-waveband film system on calcium fluoride substrate
CN118291920A
